1998
DOI: 10.1042/bj3290689
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the combined effect of two linear inhibitors on a single enzyme

Abstract: Different methods for studying the concurrent effects of two linear inhibitors on a single enzyme have been published, including the fractional product of Webb, the Yonetani-Theorell plot or the method of Chou and Talalay. Recently the use of combination plots has also been advocated for this purpose. We have evaluated the applicability of these methods and found that most of them depend on assumptions about the mechanism of action of the inhibitors. If the mechanism of action is not completely understood, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…6B). As expected, both methods of evaluating the synergy between RT inhibitors are fully consistent (24). In fact, the combination of 0.2 M of 4-arylmethylpyridinone with 1 M on the AZT r -RT showed a 90% of inhibition (Fig.…”
Section: Fig 2 Inhibition Of Phosphorolytic Activity Of Wt Rt and Aztmentioning
confidence: 53%
See 2 more Smart Citations
“…6B). As expected, both methods of evaluating the synergy between RT inhibitors are fully consistent (24). In fact, the combination of 0.2 M of 4-arylmethylpyridinone with 1 M on the AZT r -RT showed a 90% of inhibition (Fig.…”
Section: Fig 2 Inhibition Of Phosphorolytic Activity Of Wt Rt and Aztmentioning
confidence: 53%
“…6). In this plot, parallel lines are found if inhibitors do no interact, whereas intersecting lines are found if both inhibitors act synergistically (24). From this plot it can be concluded that in the presence of ATP the interaction is at least 10-fold greater than in its absence, as judged by the abscissa intersection points of both graphs.…”
Section: Fig 2 Inhibition Of Phosphorolytic Activity Of Wt Rt and Aztmentioning
confidence: 61%
See 1 more Smart Citation
“…The combination of Ad-XIAP-as and Apo2L.0 increased the median survival to 130 days (P ¼ 0.0006, compared with Ad-DE1). Synergy is difficult to evaluate in vivo, but the fractional product method 33 may be applied when the single effects are expressed as ratios of gains in survival, which correspond to values in the range of 1.3 for either treatment alone. The predicted increase in survival with co-treatment can then be calculated as 1.69, which is below the doubling of median survival observed with co-treatment ( Figure 9).…”
Section: Role Of Nf-kb During Ad-xiap-as-induced Apoptosismentioning
confidence: 99%
“…If the two inhibitors bind in mutually exclusive fashion, a will be infinite (a ¼ ? ), and in the Yonetani-Theorell method, the most popular way of evaluating the interaction between two enzyme inhibitors, it will be observed that plotting 1/v ij against [I] at fixed [J] would result in parallel straight lines (34). In this case, I and J respectively represent NADP þ and chlorogenic acid.…”
Section: Resultsmentioning
confidence: 99%